Delinquents and debutantes : twentieth-century American girls' cultures - Inness, Sherrie A. (New York University Press, 1998)
The contributors, including such leading scholars as Vicki L. Ruiz, Jennifer Scanlon, and Miriam Formanek-Brunell, examine myriad ways in which a variety of discourses and activities from popular girls' magazines and advertisements to babysitting and the Girl Scouts help form girls' experiences of what it means to be a girl, and later a woman, in our society. The essays address such topics as board games and the socialization of adolescent girls, dolls and political ideologies, Nancy Drew and the Filipina American experience, the queering of girls' detective fiction, and female juvenile delinquency to demonstrate how cultural discourses shape both the young and teenage girl in America. Although girls' culture has until now received comparatively little attention from scholars, this work confirms that understanding the culture of girls is essential to understanding how gender works in our society. Making a significant contribution to a long-neglected area of social and cultural inquiry, Delinquents and Debutantes will be of central interest to those in women's studies, American studies, history, literature, and cultural studies.--Publisher description.